Antibody engineering to evaluate binding, internalisation, and intracellular routing of tumour-targeting fusion proteins - Karaan, Maryam (Department of Health and Rehabilitation Sciences, 2024)
Breast cancer is a major global health crisis, particularly affecting women, and triple-negative breast cancer (TNBC) is an aggressive subtype with limited treatment options. TNBC is challenging to treat due to the lack of specific therapeutic markers such as estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). Current treatments primarily involve chemotherapy, radiotherapy, and surgery, as targeted therapies are limited. TNBC also exhibits significant heterogeneity among patients, emphasizing the need for precise diagnostic and therapeutic approaches. Immunotherapy, the manipulation of the immune system to target diseases, holds promise for precision medicine. Antibody-drug conjugates (ADCs) use antibodies to deliver drugs selectively. This study focused on a novel recombinant fusion protein format for ADCs using a single chain variable fragment (scFv) specific to chondroitin sulphate proteoglycan 4 (CSPG4), a tumour-associated antigen often overexpressed in TNBC. The scFv antibody derivative was genetically fused to a SNAP-tag, enabling stable and site-specific conjugation of the scFv to diagnostic and therapeutic substrates. To enhance antigen binding, internalisation, and therapeutic efficacy, a bivalent scFv fusion protein was created in tandem with the standard monovalent fusion protein. In vitro experiments using fluorophores and the cytotoxin, monomethyl auristatin F (AURIF), demonstrated that the bivalent fusion protein exhibited improved binding, faster uptake, and efficient release of the conjugate within target cells. Colocalization analysis revealed that the fusion proteins were routed to the lysosomal degradation pathway which is essential for the functionality of ADCs. The cell viability assays revealed that the enhanced binding and uptake of the bivalent fusion protein resulted in a more potent cytotoxic effect on antigen-positive TNBC cells. This study successfully compared mono- and bivalent αCSPG4-SNAP fusion proteins, revealing the superiority of the bivalent format in antigen binding and targeted drug delivery. It also, for the first time, explored the intracellular routing of scFv SNAP-tag fusion proteins upon uptake. The findings may influence the design of future scFv-based immunotherapeutics, possibly resulting in the incorporation of multiple scFv domains for increased efficacy. Furthermore, the diagnostic potential of these fusion proteins, aiding in prognosis prediction and patient responsiveness to targeted therapies have been highlighted. The versatility of SNAP-tag technology makes it relatively easy to transform immunodiagnostic fusion proteins into immunotherapeutic tools, potentially advancing TNBC management. In summary, this study contributes to the development of precision medicine tools for TNBC, addressing its complex nature and limited treatment options. The bivalent fusion protein format shows promise for improved TNBC therapy, offering a new avenue for research and potential clinical applications.